Analysis of The Influence of Effectiveness, Reliability and Competence on The Performance of The Central Legal and Credit Administration Sistem with Organizational Culture as A Moderating Variable - Soemitra, Andri; Arif, Muhammad; Arif, Edwin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to analyze how the influence of effectiveness, reliability, competence on the performance of the Central Legal and Credit Administration (CLCA) which is moderated by organizational culture. The approach used is quantitative research. The sample in this study were employees who were directly related to the CLCA system with a total sample of 93 participants. The instrument used to obtain data is a questionnaire with a Likert scale. Data analysis and testing were carried out using moderated regression which was processed using SPPS software version 25. The test results proved that effectiveness and competence did not have a positive and significant effect on the performance of the CLCA system, while reliability and organizational culture had a positive and significant effect on the performance of the CLCA system. Effectiveness and competence on the performance of the CLCA system moderated by Organizational Culture had a positive and significant effect, while reliability on the performance of the CLCA system moderated by Organizational Culture had a negative and significant effect. The effectiveness, reliability, competence, and organizational culture simultaneously have a positive and significant effect on the performance of the CLCA system.